Serratus Anterior Contraction During Resisted Arm Extension (GravityFit) Assessed by MRI - Owen, Patrick J.; Rantalainen, Timo; Scheuring, Richard A.; Belavy, Daniel L. (Frontiers in Physiology, 2019)
Background: Scapular stabilisation is a common focus of shoulder rehabilitation. Objective: Examine contraction of serratus anterior during a bilateral arm extension exercise with axial compression using an exercise device (GravityFit) by magnetic resonance imaging (MRI). Methods: MRI was performed under two conditions: rest and static arm extension with axial compression. Load was set at 20% of age, sex and weight estimated bench press one-repetition maximum. A T2-weighted sequence was used to collect 14 axial images of the upper thoracic spine and shoulder bilaterally. Mean muscle length and thickness were calculated for the whole muscle and in equidistant subregions of the muscle in its anterior (superficial), central and posterior (deep) portions. Results: Nine participants without a history of shoulder or spine pathology were included. When compared to rest, arm extension with the exercise device led to 11% increased overall muscle thickness (P = 0.019) and 6.1% decreased overall muscle length (P = 0.001). Regionally, thickness increased in anterior (superficial, +19%; P = 0.024) and central (+17%; P = 0.009) portions of the muscle more than posterior (deep, +3.9%, P = 0.54). Conclusions: Contraction of serratus anterior occurred during static arm extension with axial compression produced by a novel exercise approach, as measured via MRI. The activation of serratus anterior differed across its length with greater contraction of the anterior and central portions. This may indicate compartmentalisation of function within this muscle. Overall, the proof-of-principle findings justify the use of this exercise approach for the activation of serratus anterior.